Group Psychotherapy as a Neural Exercise: Bridging Polyvagal Theory and Attachment Theory. Issue 2 (3rd April 2017) - Flores, Philip J.; Porges, Stephen W.
ABSTRACT: Attachment theory has expanded from a theory of child development into a more complex and clinically relevant psychotherapy model for adults. Polyvagal theory (Porges, 1995, 2007, 2011), with its innovative and paradigm-shifting perspectives on the evolution and development of the neural circuits underlying co-regulation via spontaneous social engagement behaviors, provides a corresponding perspective of the neural mechanisms through which attachment theory can be applied to the practice of group psychotherapy. The group, informed by polyvagal theory, functions as an ideal "neural exercise" to promote the biobehavioral adjustments of several psychosocial processes that are associated with attachment styles, emotion regulation, stress reactivity, and social relationships. The current article will present clinical examples of how a well-managed therapy group can provide opportunities for exercising the relevant neural pathways involved in social engagement behaviors. We will demonstrate how the synchronous interaction between physiological and emotional state regulation can reciprocally and prospectively have positive impact on group members and lead to more optimal social behavior both in and out of the therapy group.